Smart Catering Canteen School (SCCS) using Streamlit - Suryasatriya Trihandaru; Hanna Arini Parhusip; Mitchella Sinta Larasati (Jurnal Sistem Informasi Bisnis, 2025)
The school canteen faced service problems of as many as 1000 students in a short break period, especially when everything had to be done manually on business processes, especially payments. The method that has existed so far is to use Google Form to place menu orders and manually pay all verified customers which causes delays and errors. Therefore, this study aims to create a business information system for canteens called the Smart Canteen System (SCCS) which uses Optical Character Recognition (OCR) and Natural Language Processing (NLP) to be able to automate payment verification and provide sequences. This SCCS business information system will convert proof of payment from text to text and processed so that the validity of the proof of payment can be proven. With the Stremlit platform, the management process can be carried out in real time and reports can be carried out immediately. With this verification, SCCS provides the main result, namely efficiency, reducing errors in business processes in the canteen. Work that was originally done manually in 2 days became 5-10 minutes in the same process.